Flapping wing mechanism for micro aerial vehicles - Yeo, Janan Yul Chen. (2009)
Micro aerial vehicles (MAVs) are defined as vehicles capable of flight not exceeding 15 cm in max dimensions. In recent times, interest in unmanned aerial vehicles of relative smaller dimensions – micro aerial vehicles have spurned a trend in the development of suitable propulsion platforms. Many have looked to nature for an answer, as the flapping flight ability of birds and insects continue to captivate biological scientists and researchers. One of the more promising propulsion mechanisms identified is that of flapping wings in plunging motions with restricted oscillatory movements. Whilst extensive research has been done on the applicability of a bi-plane configured flapping wing mechanism on micro-aerial vehicles, the majority of this work has been concentrated solely on the computational aspects. Experimental research is limited to the pioneers of the bi-plane flapping wing design: KD Jones and team. It is with this mindset that the author has chosen this project where the design, manufacture and experimental testing of a bi-plane configured flapping wing propulsion mechanism are successfully accomplished.In this report, the design and manufacture of a bi-plane configured flapping wing propulsion mechanism capable of flapping in counter-phase and in perfect symmetry is described. The thrust generation ability of this flapping wing propulsion mechanism is obtained with different sets of airfoils under varying flapping frequencies. Finally, the wake velocity profiles generated by the different set of airfoils under varying flapping frequencies are plotted and analysed. A correlation between the thrust generated and the wake velocity profile generated is drawn and the suitability of such a mechanism as a propulsion platform in MAVs is assessed.